Exosomes Derived From Adipose-Derived Mesenchymal Stem Cells Ameliorate Radiation-Induced Brain Injury by Activating the SIRT1 Pathway - Liu, Mengdong; Yang, Yunshu; Zhao, Bin; Yang, Yuefan; Wang, Jing; Shen, Kuo; Yang, Xuekang; Hu, Dahai; Zheng, Guoxu; Han, Juntao (Frontiers in Cell and Developmental Biology, 2021)
Objective：Studies have shown that the therapeutic effects of mesenchymal stem cells are mediated in a paracrine manner, mainly through extracellular vesicles such as exosomes. Here, we designed a study to investigate whether exosomes derived from adipose-derived mesenchymal stem cells (ADMSC-Exos) had protective effects in a rat model of radiation-induced brain injury and in microglia. Methods：Male adult Sprague-Dawley rats were randomly divided into three groups: the control group, the radiation group (30Gy), and the radiation+exosomes group (30 Gy+100ug exosomes). Meanwhile, microglia were divided into four groups: the control group, the radiation group (10Gy), the radiation+exosomes group (10Gy+4ug exosomes), and radiation+exosomes+EX527 group (10Gy+4ug exosomes+100nM EX527). Tissue samples and the levels of oxidative stress and inflammatory factors in each group were compared. Results：Statistical analysis showed that after irradiation, ADMSC-Exos intervention in vivo significantly reduced the levels of caspase-3, MDA, 8-OHdG, TNF-α, IL-4 and promoted the recovery of SOD，CAT，IL-4, IL-10. Moreover, ADMSC-Exos intervention inhibited microglial infiltration and promoted the expression of SIRT1. Furthermore, the results in vitro showed that the above effects of ADMSC-Exos could be reversed by SIRT-1 inhibitor EX527. Conclusion：This study demonstrated that ADMSC-Exos exerted protective effects against radiation-induced brain injury by reducing oxidative stress, inflammation and microglial infiltration via activating the SIRT1 pathway. ADMSC-Exos may serve as a promising therapeutic tool for radiation-induced brain injury.